Humic acid and sulfur integration enhance growth and yield-related traits of Brassica napus L. (15th June 2023) - Imran,; Amanullah,; Al Tawaha, Abdel Rahman
Abstract: Humic acid and sulfur play an important role in enhancing the growth and yield-related traits of Brassica napus L. The objectives of our study to evaluate the effect of different levels of S and HA on the yield of rapeseed ( Brassica napus L.). Demonstrative plots were sown for two consecutive seasons and treated with five levels of Sulfur (S) i.e., 0, 30, 45, 60, and 75 kg ha −1 and four levels of humic acid (HA), 0, 5, 10, and 15 kg ha −1 . Factorial combination of S and HA levels was engaged in a randomized complete block design using three replications. Results indicated that higher plant height and siliques plant −1 were documented upon S (45 kg ha −1 ) application. On the other hand, 60 kg S ha −1 treatments resulted in higher siliques m −2, grains per silique, 1000-seed weight and seed yield. However, the highest biological yield was produced with 75 kg S ha −1 . Among HA levels, the tallest plants, more siliques plant −1, maximum grain yield and HI were recorded with 15 kg HA ha −1 application. Conclusively the response of rapeseed was significant to combine application of S and HA and the highest seed yield and HI was higher with the integration of 45 kg S ha −1 and 10 kg HA ha −1 . It could be concluded that rapeseed should be treated with sulfur and humic acid at the rate of 45 and 10 kg ha −1 for higher yield, yield components, and quality of rapeseed under the northern climatic scenario.